Implementation of a low power electroliner using solar panels - Arbito Chica , Fernando (2025)
The generation of electrical energy through a photovoltaic system that takes advantage of solar radiation is possible to supply electricity to electrical transport means. The objective is to design a low-power electroliner that uses solar energy to provide services to students who use electric vehicles. The quantitative approach is classified as proactive. The design is not experimental. The collection of information was carried out using documentary analysis techniques on the energy performance of existing electric lines. The population is made up of different models and types of electric vehicles. The hallazgos demonstrate that, although the electroliner represents a sustainable solution to promote the use of clean energy, it also has an environmental impact associated throughout its life cycle, from the manufacture of components to their eventual recycling. It is concluded that the study highlights the importance of adopting innovative solutions such as solar electrolines to promote a more sustainable future in transportation